Women in the military and in armed conflict - Carreiras, Helena; Kümmel, Gerhard (Schriftenreihe des Sozialwissenschaftlichen Instituts der Bundeswehr, 2008)
Foreword / Helena Carreiras & Gerhard K(c)ơmmel -- Women in combat: reconsidering the case against the deployment of women in combat-support and combat units / Stephan Maninger -- Off limits: the cults of the body and social homogeneity as discoursive weapons targeting gender integration in the military / Helena Carreiras & Gerhard K(c)ơmmel -- Unsung heroes: women's contributions in the military and why their song goes unsung / Irene Jung Fiala -- About intervening in vulnerable societies: gender in military peacekeeping of the Bundeswehr / Cordula Dittmer & Maja Apelt -- Women in the Netherlands armed forces / Ren(c)♭ Moelker & Jolanda Bosch -- Defying the prohibited arena: women in the UAE military / Suaad Zayed Al-Oraimi -- From loyalty to dissent: how military women respond to integration dilemmas / Helena Carreiras -- Chivalry in the military / Gerhard K(c)ơmmel -- The militarization of gender and sexuality in the Iraq war / Lindsey Feitz & Joane Nagel -- Violence against women in conflict zones / Ceyda Kuloglu